Development of New Preventive and Therapeutic Vaccines for Tuberculosis - Kwon, Bo-Eun; Ahn, Jae-Hee; Min, Seunghwan; Kim, Hyeongseop; Seo, Jungheun; Yeo, Sang-Gu; Ko, Hyun-Jeong (Immune network, 2018)
Tuberculosis (TB) is a contagious disease that has been responsible for the death of one billion people in the last 200 years. Until now, the only vaccine approved for the prevention of TB is Bacillus Calmette-Guérin (BCG), which is prepared by attenuating . However, one of the limitations of BCG is that its preventive effect against pulmonary TB varies from person to person. Therefore, there arises a need for a new TB vaccine to replace or supplement BCG. In this review, we have summarized the findings of current clinical trials on preventive and therapeutic TB vaccine candidates. In addition, we have discussed a novel vaccination approach using the cell-based vaccine presenting early secretory antigenic target-6 (ESAT-6), which is a potent immunogenic antigen. The role of ESAT-6 in hosts has also been described.